2010
DOI: 10.1007/s11606-010-1501-z
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Actions on Electronic Referral Communication in a Multispecialty Outpatient Setting

Abstract: OBJECTIVES: Electronic health records (EHR) enable transmission and tracking of referrals between primarycare practitioners (PCPs) and subspecialists. We used an EHR to examine follow-up actions on electronic referral communication in a large multispecialty VA facility. METHODS: We retrieved outpatient referrals to five subspecialties between October 2006 and December 2007, and queried the EHR to determine their status: completed, discontinued (returned to PCP), or unresolved (no action taken by subspecialist)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 25 publications
0
49
0
Order By: Relevance
“…8,15,[17][18][19][20] EMRs can also be applied specifically to facilitate the referral process, one of the most common and important types of primary-specialty care communication. 21,22 The Veterans Health Administration (VHA) is a fully integrated healthcare system with a well-developed, comprehensive EMR system. The VHA's EMR is the dominant method of connecting primary and specialty care at the VHA, serving as the vehicle for conveying requests from primary care for specialty consults as well as specialist recommendations back to primary care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,15,[17][18][19][20] EMRs can also be applied specifically to facilitate the referral process, one of the most common and important types of primary-specialty care communication. 21,22 The Veterans Health Administration (VHA) is a fully integrated healthcare system with a well-developed, comprehensive EMR system. The VHA's EMR is the dominant method of connecting primary and specialty care at the VHA, serving as the vehicle for conveying requests from primary care for specialty consults as well as specialist recommendations back to primary care.…”
Section: Introductionmentioning
confidence: 99%
“…One study conducted within the VHA, however, identified a subset of cases evidencing unexplained breakdowns in primary-specialty referral communication. 21 The EMR alone, therefore, may not be "enough" to solve the problems in primary-specialty communication. 4,9,13,23 Little is known about referral communication between primary and specialty care in the VHA and similar healthcare systems that already benefit from an integrated delivery system and shared EMRs.…”
Section: Introductionmentioning
confidence: 99%
“…However, even when supported by technology, referral communication between PCPs and specialists can be less than satisfactory 24 and in the past has led to new communication challenges and unintended consequences, often related to non-technical factors. 11,25 Thus, methodological approaches for implementing and evaluating outcomes of health IT-related communication interventions need to address both technological (software/ hardware) and non-technological Bsocial^(e.g., organizational components, people and workflow) 26 contextual factors. These approaches, for instance, must be grounded in an understanding of how referral processes fit within the complex Bsociotechnical^context of health IT-enabled care.…”
Section: Teaching Commentarymentioning
confidence: 99%
“…These approaches, for instance, must be grounded in an understanding of how referral processes fit within the complex Bsociotechnical^context of health IT-enabled care. 25,27 Most existing implementation frameworks are not sufficient to specifically evaluate health IT-based quality improvement or patient safety-related interventions. To effectively assess health IT-based interventions, frameworks or approaches must consider technology within the larger sociotechnical system in which it is implemented.…”
Section: Teaching Commentarymentioning
confidence: 99%
See 1 more Smart Citation